Developing green supplier selection procedure: A DEA approach - Wen, U P; Chi, J M (2010 IEEE 17Th International Conference on Industrial Engineering and Engineering Management, 2010)
This study considers a criteria set including green, traditional, and partnership issues for the green supplier selection problem. The criteria set takes carbon footprint into account, because the international regulations have paid much attention on the carbon footprint exposure in recent years. Moreover, most of the studies of green supplier selection use Analytical Hierarchical Process (AHP) and Analytical Network Process (ANP) to evaluate the suppliers. However, according to the limitation of this methodology, they can only deal with the small size problem. This study introduces Data Envelopment Analysis (DEA) into assessment, and combined with AHP to establish an integrated model. Furthermore, the assurance region is implemented not only to take the opinion of decision makers into consideration, but to increase the discriminating power of the model. Merging with the above criteria set, this evaluating model turns into a practical integrated framework of green supplier selection.